2017
DOI: 10.1371/journal.pone.0173818
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes of the respiratory microbiota and its relationship to fecal and blood microbiota in healthy young cats

Abstract: Advances in the field of metagenomics using culture-independent methods of microbial identification have allowed characterization of rich and diverse communities of bacteria in the lungs of healthy humans, mice, dogs, sheep and pigs. These data challenge the long held belief that the lungs are sterile and microbial colonization is synonymous with pathology. Studies in humans and animals demonstrate differences in the composition of airway microbiota in health versus disease suggesting respiratory dysbiosis occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(103 citation statements)
references
References 50 publications
2
101
0
Order By: Relevance
“…We note, that some phyla are enriched by the applied resuscitation strategy according to the OTUs combined abundancy (Table 1). Other studies also identified Proteobacteria as predominant in the blood of healthy individuals [14], healthy broilers [16] and cats [17].…”
Section: Resultsmentioning
confidence: 86%
“…We note, that some phyla are enriched by the applied resuscitation strategy according to the OTUs combined abundancy (Table 1). Other studies also identified Proteobacteria as predominant in the blood of healthy individuals [14], healthy broilers [16] and cats [17].…”
Section: Resultsmentioning
confidence: 86%
“…Samples were collected as previously described (Vientos-Plotts et al, 2017). Briefly, cats were anesthetized and a sterile cotton-tip swab was inserted rectally, while avoiding contact with the perianal area.…”
Section: Methodsmentioning
confidence: 99%
“…However, recent studies using sequencing of microbial 16S rRNA amplicons (Sidiq et al, 2016) have demonstrated that healthy humans (Charlson et al, 2012), dogs (Ericsson et al, 2016), and cats (Vientos-Plotts et al, 2017) harbor rich, complex commensal microbial populations in the respiratory tract. There is increasing evidence that commensal microbes play a critical role in the maturation, education, and function of the immune system and, in particular, regulation of inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%
“…Specimens should be directly frozen or added to RNA later stabilizer solution after collection and treatment and then transferred to −80°C for storage. To avoid factors that may influence the results, such as reagents and batches, entire specimens should be collected and then tested together . The order of specimen processing should be randomized.…”
Section: Management Of the Gut Microbiota Biobankmentioning
confidence: 99%